Examining associations between medical fear and perceptions of provider trust, provider empathy, and medical mistrust among college-attending young adults - Sarah C. M. Morton; Ashley Miller; Robin S. Everhart (PLoS ONE, 2025)
Objective The current study examined associations between various dimensions of medical fear (e.g., blood, mutilation, sharp objects, injection/blood draws, examinations/symptoms) and perceptions of provider trust, provider empathy, healthcare system mistrust, and attitudes toward medical care-seeking. Additionally, we explored the associations between different dimensions of medical fear and medical care engagement. Methods A convenience sample of 479 young adults (18–26 years) attending a large, urban Mid-Atlantic university completed a cross-sectional online survey during the fall of 2022 assessing medical fears, provider trust, perceptions of provider empathy, medical care-seeking attitudes, and medical mistrust. Participants with medical fears (n = 211) answered an additional open-ended question regarding medical care engagement. Multiple regression models were used to examine associations between medical fear dimensions and outcome measures. A binary logistic regression was performed to examine the likelihood of health care engagement based on different medical fear dimensions. Statistical significance was set at p < .05. Results Participants identified as 75.8% female (n = 363), 47.0% White (n = 219), and 25.7% (n = 122) reported having a chronic illness. Increasing levels of mutilation fear were significantly associated with lower ratings of provider trust (β = −.286, p < .001) and empathy (β = −.172, p = .010), as well as more medical mistrust (β = .227, p < .001). None of the five medical fear dimensions were significantly associated with medical engagement. Conclusions Findings highlight the role of mutilation fears in patient-provider relationships and views about the healthcare system in general. While these fears were not associated with medical care avoidance in our study, their association with patient-provider relationships may have implications for adherence to medical recommendations and health outcomes. Patient-centered collaborative care that takes medical fears into consideration may help strengthen patient-provider relationships and mitigate potential negative health outcomes.